2021
DOI: 10.24042/kons.v8i2.8778
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement during pandemic COVID-19 and its implications for guidance and counseling

Abstract: Student engagement is a condition of the extent to which students play an active role in the learning process by focusing on time, energy, mind, effort, feelings and making it happen in action to complete their academic tasks completely. This study aims to explore and find out the level of student engagement in the Covid-19 pandemic period seen from gender differences and the school level. Quantitative descriptive research with this survey design involves 469 students, 245 students of the junior high school, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Based on the data that has been presented, it can be seen that in the implementation of guidance and counseling, school counselors mostly use media in the form of WhatsApp applications in the implementation of their services [18]. Then if it is reviewed based on implementation, it shows that the implementation of guidance services is higher than guidance, but when viewed from the achievement of goals, it is found that the purpose of counseling is higher than guidance [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the data that has been presented, it can be seen that in the implementation of guidance and counseling, school counselors mostly use media in the form of WhatsApp applications in the implementation of their services [18]. Then if it is reviewed based on implementation, it shows that the implementation of guidance services is higher than guidance, but when viewed from the achievement of goals, it is found that the purpose of counseling is higher than guidance [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…From the results of this study, it can be assumed that the level of learner engagement in post pandemic was almost the same as that before the crisis. However, the importance of learner engagement should not be underestimated because effective engagement can predict learners" success, and it can potentially help to close learning gaps during the crisis (Nugroho et al, 2021). In the new normal, when learners can return for face-to-face instruction, teachers need to provide a balanced student engagement strategy to be effective during the Covid-19 pandemic and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the COVID-19 pandemic has resulted in radical changes and demands to be able to adapt quickly (Xu, Li, & Wei, 2022;Zheng, Khan, & Hussain, 2020). One of the changes that occurred was the implementation of the learning process which underwent several policy changes, for sure this condition had a significant impact (Nugroho, Kusumawati, & Wahyuningsih, 2021). This happens because of simultaneous changes in several aspects without being accompanied by readiness to face these conditions (Martoredjo, 2020).…”
Section: Introductionmentioning
confidence: 99%